Pengaruh Komponen Value Added Intellectual Coefficient (VAIC™) terhadap Kinerja Keuangan Perusahaan Transportasi dan Logistik di Indonesia - Zahiro Safinah; Ira Septriana; Enny Susilowati Mardjono; Bambang Minarso (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of intellectual capital measured through Structural Capital Value Added (STVA), Value Added Human Capital (VAHC), and Value Added Capital Employed (VACE) on the financial performance of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. This research was conducted because previous studies have yielded inconsistent results regarding the impact of intellectual capital on financial performance. Transportation and logistics companies were selected as a novel research focus because they have rarely been studied as subjects of intellectual capital research. Financial performance was measured using Return on Equity (ROE). This study employs a quantitative approach using panel data regression analyzed with Eviews 14. The sample was selected using purposive sampling, resulting in 78 observations. The analysis indicates that, individually, VACE and VAHC have a positive effect on financial performance, whereas STVA does not have a significant effect. However, collectively, STVA, VAHC, and VACE have a positive effect on financial performance, indicating that the integrated management of structural capital, human capital, and capital employed can create added value and support improvements in a company’s financial performance. These findings suggest that the creation of added value in the transportation and logistics sector is driven more by the utilization of financial capital and human capital than by structural capital.